The variation of bird diversity in various oil palm land cover in North Mamuju, West Sulawesi, Indonesia - Sitti Ramlah; YANTO SANTOSA; NYOTO SANTOSO; SITI BADRIYAH RUSHAYATI (Society for Indonesian Biodiversity, 2021)
Abstract. Ramlah S, Santosa Y, Santoso N, Rushayati SB. 2021. The variation of bird diversity in various oil palm land cover in North Mamuju, West Sulawesi, Indonesia. Biodiversitas 22: 3068-3074. The development of oil palm plantations provides various positive impacts. On the other hand, this development is suspected to bring negative impacts on biodiversity, especially reducing bird species diversity. Based on the other research, well-managed oil palm plantations that maintain high conservation value areas have high species diversity. This study aimed to identify bird species diversity in different types of oil palm plantation land covers in North Mamuju. Data observation of bird species was performed using the transect method. There were 4 transects on each land cover. The results of this study showed that the young oil palm area had a high index of diversity and species richness. The high species diversity in the young palm area was caused by habitat variations. There was a water flow that provides more feed sources. The distance between the young oil palm area and secondary forest area affected the number of species, species richness and diversity of bird species. The category of insectivore guild which included aerial insectivores and insectivores was the dominant guild in all types of land cover, both in the number of species and the number of individual abundances.